Low level of microplastic contamination in wild fish from an urban estuary. (November 2020) - Lin, Lang; Ma, Li-Sha; Li, Heng-Xiang; Pan, Yun-Feng; Liu, Shan; Zhang, Li; Peng, Jin-Ping; Fok, Lincoln; Xu, Xiang-Rong; He, Wei-Hong
Abstract: Microplastic accumulation in estuarine environments is considered the dominant input of land-based plastics into the oceans. In this study, the level of microplastic contamination was evaluated in 26 species of wild fish from the Pearl River Estuary, South China. Results showed that microplastics abundance ranged from 0.17 items individual −1 ( Boleophthalmus pectinirostris & Acanthogobius flavimanus ) to 1.33 items individual −1 ( Plectorhynchus cinctus ) among different species. The distribution of microplastic abundance in the gills and gastrointestinal tracts was not significantly different. Microplastics in gills are strongly related to the filtration area of gills in 15 fish species. Fibers were the dominant shapes accounting for 93.45% of the total shapes. The majority of microplastics were <3 mm in size. The most common polymer composition was polyethylene terephthalate (38.2%) and the most common color was black (30.36%). The findings of this study provide baseline data for microplastic contamination in wild fish from an urban estuary. Graphical abstract: Unlabelled Image Highlights: Microplastics were widely detected in 26 fish species. Fibers were the dominant type of microplastics. Gill was an important organ for microplastic accumulation. Microplastic ingestion by fish might be induced by the physiochemical properties.